The overexpression of insect endogenous microRNA in transgenic rice inhibits the pupation of Chilo suppressalis and Cnaphalocrocis medinalis. Issue 9 (12th May 2021) - Wen, Ning; Chen, Junjie; Chen, Geng; Du, Lixiao; Chen, Hao; Li, Yunhe; Peng, Yufa; Yang, Xiaowei; Han, Lanzhi
Abstract: BACKGROUND: Chilo suppressalis and Cnaphalocrocis medinalis are destructive rice pests co‐occurring in major rice‐growing areas in China. RNA interference (RNAi)‐based insect‐resistant genetically engineered (IRGE) crops provide a promising approach for pest management by suppressing gene expression or translation. A microRNA (miRNA)‐mediated IRGE rice line expressing endogenous Chilo suppressalis miRNA Csu‐novel‐260, showing significant resistance against Chilo suppressalis, provides an attractive control strategy for Chilo suppressalis by suppressing the expression of the disembodied ( dib ) gene expression . However, whether this transgenic line also shows the resistance against Cnaphalocrocis medinalis remains unknown. RESULTS: A spatiotemporal expression analysis of Csu‐novel‐260 in the transgenic rice line was performed by quantitative reverse transcription polymerase chain reaction (qRT‐PCR) to determine the paddy field pest exposure dose. In diet feeding assays, a chemically synthesized Csu‐novel‐260 agomir at 200 fmol g –1 significantly inhibited Chilo suppressalis pupation. However, larval development, survival and pupal weight were not significantly affected. Additionally, the transgenic line significantly affected Cnaphalocrocis medinalis pupation but not larval survival. The qRT‐PCR showed that Csdib and Cmdib expression levels were significantly suppressed when the two pests fed on the transgenic line. Additionally, the transgenic line significantly decreased Cry1C‐resistant and Cry1C‐susceptible Chilo suppressalis larval survival in detached rice tissue feeding assays, indicating that Cry1C‐resistant Chilo suppressalis was not cross‐resistant to Csu‐novel‐260 expressed in miRNA‐mediated IRGE rice. CONCLUSION: Our study demonstrated that miRNA‐mediated IRGE rice significantly inhibited Chilo suppressalis and Cnaphalocrocis medinalis pupation. The results provide a new viewpoint for the application of RNAi‐based plants and the inspiration for environmental risk assessment. Abstract : The microRNA‐mediated transgenic rice line significantly inhibits the pupation of Chilo suppressalis and Cnaphalocrocis medinalis. © 2021 Society of Chemical Industry.